Mediastinal Gastroenteric Duplication Cyst Presenting as Recurrent Retropharyngeal Abscess in a Child - Kini, Pushpa Gurudas; Kamath, Ganesh S; Kumar, Sandeep; Nayak M, Deepak; Moras, Karen; Kini, Priyanka (Journal of Nepal Paediatric Society, 2021)
Mediastinal duplication cyst is a rare cause of mediastinal mass in early infancy. Recurrent retropharyngeal abscess is an uncommon presentation of mediastinal duplication cyst. We report a case of mediastinal duplication cyst in a nine year old girl who presented with recurrent retropharyngeal abscess. Surgical excision was performed successfully. The mode of clinical presentation and management has been discussed.